Synthesis of some cis-4,4-dimethyl-2-isopropenylcyclopentane derivatives as potential intermediates towards the protoilludane skeleton - Mdachi , SJM (Tanzania Journal of Science, 2021)
The three gem-dimethyl-substituted cyclopentane derivatives 1-(2-propionyl)-4,4-dimethyl-2-isopropenylcyclopentane, 2-isopropenyl-4,4-dimethylcyclopentanecarboxyaldehyde and 1-hydroxy- methyl-2-isopropenyl-4,4-dimethylcyclopentane have been synthesized employing a thermally induced ene reaction as a key step. Each of the three compounds has been obtained predominantly as the cis isomer. The successful synthesis of these compounds affords opportunities for their further ellaboration towards sesquiterpenes of the protoilludane skeleton.